All-Red-Light Photoswitching of Indirubin Controlled by Supramolecular Interactions - Thumser, Stefan; Köttner, Laura; Hoffmann, Nadine; Mayer, Peter; Dube, Henry (Journal of the American Chemical Society, 2021)
Red-light responsiveness of photoswitches is a highly desired property for many important application areas such as biology or material sciences. The main approach to elicit this property uses strategic substitution of long-known photoswitch motives such as azobenzenes or diarylethenes. Only very few photoswitches possess inherent red-light absorption of their core chromophore structures. Here, we present a strategy to convert the long-known purple indirubin dye into a prolific red-light-responsive photoswitch. In a supramolecular approach, its photochromism can be changed from a negative to a positive one, while at the same time, significantly higher yields of the metastable E-isomer are obtained upon irradiation. E- to Z-photoisomerization can then also be induced by red light of longer wavelengths. Indirubin therefore represents a unique example of reversible photoswitching using entirely red light for both switching directions.
CRIS-Team WoS Importer:2021-11-19